2019
DOI: 10.1002/cche.10182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alternative irrigation practices on rice quality

Abstract: Background and objectives:Current global concerns about water scarcity present a need to investigate more water-efficient rice production methods. Alternate wetting and drying (AWD) is fast emerging as a water-saving irrigation practice, but its effects on rice quality are largely unknown. To ascertain the impact of water-saving irrigation practices on rice quality, three irrigation treatments, namely continuous flooding with cascade delivery (four fields); continuous flooding with multiple-inlet delivery (fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Efforts are being made to grow rice under semi-irrigated (aerobic) conditions (Dharmappa et al ., 2019). Irrigation practices like furrow and multiple inlet irrigation, alternate wetting and drying and overhead sprinklers have gained interest to optimize water use (Bouman et al ., 2007; Girsang et al ., 2019; Graham-Acquaah et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts are being made to grow rice under semi-irrigated (aerobic) conditions (Dharmappa et al ., 2019). Irrigation practices like furrow and multiple inlet irrigation, alternate wetting and drying and overhead sprinklers have gained interest to optimize water use (Bouman et al ., 2007; Girsang et al ., 2019; Graham-Acquaah et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Graham‐Acquaah et al. (2019) reported that SV was lower in rice grown with AWD and attributed the variation to a possible change in amylose content due to water stress. Our results revealed that irrigation treatments did not affect amylose content in three of the four cultivars.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, grain in the AWD treatment in Graham‐Acquaah et al. (2019) study may have experienced higher temperatures during the reproductive stage compared to the conventional irrigation treatments, altering grain quality.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations